Women’s Accessibility and Production of Gender-Responsive Policies through Thematic Musrenbang in Malang City, Indonesia - Prastiwi, Juwita Hayyuning; Yunas, Novy Setia (Universitas Muhammadiyah Yogyakarta, 2025)
The ineffectiveness of the Deliberation of Development Planning/Musyawarah Perencanaan Pembangunan (Musrenbang) forums to serve the aspirations of citizens, particularly the marginalized groups, has prompted several local governments in Indonesia to innovate in holding Thematic Musrenbang forums, one of them in Malang City. This research aims to describe the accessibility and role of women's groups in the Women’s Thematic Musrenbang and how gender-responsive policies are created in these activities. From a feminist perspective, this research uses qualitative methods with FGDs, in-depth interviews, participatory observation, and documentary studies as data collection methods. The results showed that women's groups in Malang City were accessible in the development planning process, which was represented by civil society organizations and community-based organizations. Substantially, some progress has been achieved through the incorporation of aspirations from Musrenbang participants. However, the absence of gender analysis within the planning process, coupled with the predominant technocratic approach and the limitations in the application of the local development planning system, has impeded the full of the objectives of the Women’s Thematic Musrenbang. This research offers a novel examination of participatory development planning in Indonesia by focusing specifically on the effectiveness of Thematic Musrenbang forums, a relatively new and under-researched approach to incorporating citizen input. Ultimately, the findings offer practical recommendations for policymakers and practitioners to improve the design and implementation of Thematic Musrenbang, ensuring these forums genuinely serve the needs and aspirations of all citizens, particularly women.